2018
DOI: 10.17265/2328-2150/2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of Immunological Activity of Achillea Millefolium Methanolic Extract on Albino Male Mice

Abstract: Achillea millefolium (Asteraceae) is a permanent herb highly recognized in traditional medicine for its anti-oxidant and anti-inflammation properties. However, studies on phytochemical constituents of A. millefolium underlying these properties are scarce. The present work focuses on examining the effect of methanol extract of A. millefolium L. on total and differential blood cells account on albino male mice. The results showed the methanol extract increased the account of lymphocyte, and monocyte cells, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Miers (family: Menispermaceae) ( Mathew and Kuttan, 1999 ), Withania somnifera (L.) Dunal (family: Solanaceae) ( Davis and Kuttan, 2000 ), Curcuma longa L. (family: Zingiberaceae) ( Kim et al, 2014 ), Ocimum sanctum L. (family: Lamiaceae) ( Mondal et al, 2011 ), Azadirachta indica A. Juss. (family: Meliaceae) ( van der Nat et al, 1987 ), Achilla millefolium L. (family: Asteraceae) ( Mohammed Al-Ezzy et al, 2018 ), and many more are the reported herbs exhibiting excellent immunomodulatory activity. Based on our preliminary study, we focused only on the first four plants, namely, P. emblica , P. nigrum , T. cordifolia , and W. somnifera .…”
Section: Introductionmentioning
confidence: 99%
“…Miers (family: Menispermaceae) ( Mathew and Kuttan, 1999 ), Withania somnifera (L.) Dunal (family: Solanaceae) ( Davis and Kuttan, 2000 ), Curcuma longa L. (family: Zingiberaceae) ( Kim et al, 2014 ), Ocimum sanctum L. (family: Lamiaceae) ( Mondal et al, 2011 ), Azadirachta indica A. Juss. (family: Meliaceae) ( van der Nat et al, 1987 ), Achilla millefolium L. (family: Asteraceae) ( Mohammed Al-Ezzy et al, 2018 ), and many more are the reported herbs exhibiting excellent immunomodulatory activity. Based on our preliminary study, we focused only on the first four plants, namely, P. emblica , P. nigrum , T. cordifolia , and W. somnifera .…”
Section: Introductionmentioning
confidence: 99%